Mesenchymal Stem Cells for Cardiac Regeneration: Translation to Bedside Reality - Mohammad T. Elnakish; Fatemat Hassan; Duaa Dakhlallah; Clay B. Marsh; Ibrahim A. Alhaider; Mahmood Khan (Hindawi Limited, 2012)
Cardiovascular disease (CVD) is the leading cause of death worldwide. According to the World Health Organization (WHO), an estimate of 17.3 million people died from CVDs in 2008 and by 2030, the number of deaths is estimated to reach almost 23.6 million. Despite the development of a variety of treatment options, heart failure management has failed to inhibit myocardial scar formation and replace the lost cardiomyocyte mass with new functional contractile cells. This shortage is complicated by the limited ability of the heart for self-regeneration. Accordingly, novel management approaches have been introduced into the field of cardiovascular research, leading to the evolution of gene- and cell-based therapies. Stem cell-based therapy (aka, cardiomyoplasty) is a rapidly growing alternative for regenerating the damaged myocardium and attenuating ischemic heart disease. However, the optimal cell type to achieve this goal has not been established yet, even after a decade of cardiovascular stem cell research. Mesenchymal stem cells (MSCs) in particular have been extensively investigated as a potential therapeutic approach for cardiac regeneration, due to their distinctive characteristics. In this paper, we focus on the therapeutic applications of MSCs and their transition from the experimental benchside to the clinical bedside.